Improving Points Writing Skills Using the Model Cooperative Type Make A Match Cooperative Model in Elementary School Students - Dona Lestari; Yanti Yandri Kusuma; Nurhaswinda Nurhaswinda (Edumaspul: Jurnal Pendidikan, 2023)
This research is motivated by the low ability of students to write pantu. One solution to overcome this problem is to use the make a match type of cooperative learning model. The purpose of this research is to describe the planning, implementation and improvement of pantun writing skills using the make a match cooperative model in elementary schools. This research method is a classroom action research carried out in two cycles. Each cycle consists of two meetings and four stages, planning, action, observation and reflection. The subjects of this study were 12 class V students, 3 boys and 9 girls. Data collection techniques in the form of observation, documentation and tests. The results showed that students' rhyme writing skills increased in each cycle. In the pre-action obtained an average value of 55.75 with classical completeness of 25%, increased in cycle I meeting I to 59.92 with classical completeness of 50%, increased in cycle I meeting II to 73.58 with classical completeness of 66 .67%. The class average score in cycle II meeting I was 81.42 with classical completeness of 83.34% and increased in cycle II meeting II that was equal to 90.75 with classical completeness of 91.67%. Thus it can be concluded that using the cooperative learning model of the make a match type can improve the rhyme writing skills of class V students at SDN 004 Bangkinang Kota. Keywords: Model Cooperative Type Make A Match, Pantun Writing Skills, and Elementary School